PENGARUH SUBSTITUSI TEPUNG MOCAF (Modified Cassava Flour) TERHADAP MUTU KUE CUBIT - Muhammad Gilang Perkasa Alam; Suardy Suardy; Ratnawaty Fadilah (Jurnal Pendidikan Teknologi Pertanian, 2022)
This study aims to determine the best substitution between mocaf flour substitution and wheat flour and substitution of mocaf flour and breadfruit flour in making cubit cake and find out the best substitution treatment for mocaf flour with flour or mocaf flour substitution with breadfruit flour in making cubit cakes in proximate tests and organoleptic test. This research method uses a completely randomized design (CRD). The results of the study were used using ANOVA variance analysis technique with DMRT further test (Duncan multiple rate). Proximate test analysis results showed that the best treatment of mocaf flour substitution with breadfruit flour in making cubit cake was treatment using 60% mocaf flour and 40% breadfruit flour. And the results of organoleptic test analysis conducted by the panelists showed that the best treatment of substitution of mocaf flour with breadfruit flour in the making of kuecubit was the treatment using 40% mocaf flour and 60% breadfruit flour.